PENERAPAN MODEL PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI, KEAKTIFAN DAN PEMAHAMAN KONSEP PESERTA DIDIK DALAM PELAJARAN IPA TERPADU KELAS VII SMPK ST. YOHANES NELLE ST.YOHANES NELLE - Trasia Sona, Anne; Yoseph Tuta Mago, Oktavius; Boli Tematan, Yohanes (Jurnal Biogenerasi, 2024)
This study aims to improve the activeness, motivation, and understanding of learning concepts of students in Natural Science (IPA) subjects in class VII SMPK St. John Nelle by applying the Problem Based Learning (PBL) learning model. The type of research conducted is Classroom Action Research, which is designed to overcome the problems faced in the classroom. The research subjects consisted of 14 students of class VII in the odd semester of the 2024/2025 school year. The research was carried out in two cycles, where each cycle was reflected on the actions applied. The instruments used to collect data consisted of observation sheets, questionnaires, and post-tests. The results showed that the application of the problem-based learning model in Natural Science (IPA) subjects in the liveliness of students based on the assessment of discussion groups had an average of 75% while the assessment of students based on understanding the concept had an average value of 71.4%. Thus the percentage of completeness from cycle I 60% rose to 80% in the second cycle, so it can be concluded that the problem-based learning model is effective in increasing students' activeness, motivation, and understanding of concepts in Natural Science subjects.